Environmental and Health Factors for Preparing a Suitable Office Environment for Elderly Workers - Maneechote, Supat; Tuprakay, Seree; Ratcha, Mongkol; Pooworakulchai, Chaiwat; Harnphanit, Boontham; Thammapornram, Chaleeporn (Health Science Journal of Thailand, 2024)
Thailand is entering an aging society, leading to a labor shortage and an extended working age. However, the elderly still have a high prevalence of diseases such as cancer and tumors (19.61%), circulatory system diseases (15.72%), nervous system diseases (14.63%), respiratory system diseases (14.03%), and others. This research aims to identify environmental factors in the workplace that significantly influence the prevalence of these diseases and suitable for control. The research employs a mixed-methods approach. Qualitative research uses VOSviewer software to analyze bibliometric data from related research in the Scopus database to identify research gaps and compare standards such as WELL, Fitwel, CASBEE, BREEAM, DGNB, TREES, and LEED. It was found that Fitwel and WELL standards have well-distributed and comprehensive requirements. Additionally, an in-depth study was conducted to determine the causes of diseases and link them to the workplace environment by consulting with public health experts. Quantitative research employs Analytic Hierarchy Process (AHP) to analyze the importance weights of each environmental factor affecting each disease. It was found that VOC, CO2, PM2.5, and temperature are highly correlated with cancer and tumors, circulatory system diseases, all types of nervous system diseases, and respiratory system diseases. The study suggests that the minimum requirements and practices that need to be implemented include controlling VOC, CO2, PM2.5, and temperature, as well as ensuring appropriate lighting, in conjunction with legal compliance, to improve workplace health conditions.